EFFECT OF VARIATION IN THE NUMBER OF THICK SLAB ON THE SCAN TIME AND IMAGE INFORMATION ON THE EXAMINATION OF MAGNETIC RESONANCE CHOLANGIOPANCREATOGRAPHY (MRCP) - Jeniyanthi, Ni Putu Rita; Latifah, Leny; Mulyantoro, Donny Kristanto; Sudiyono, Sudiyono; Amri, Faisal (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Thick Slab is a technique used in the MRCP examination to acquire the image of the biliary system by using oblique slices in taking some parts of the image at different angles. Image quality with a thick slab technique is considered better than the thin slice since the image visualization of the bile ducts system in various parts appear more clearly. Aims: The purpose of this study is to determine the effect of variation in the number of thick slab on the scan time and image information on the MRCP and determine the most informative image with the most effective scan time as possible. Methods: This study type was an experimental study conducted in St. Elisabeth hospital Semarang. The data were in the form of 90 MRI images of biliary tract of 3 patients with 5 variations of Thick Slab (6, 12, 18, 24, 30). The image assessment was taken by 5 respondents regarding the information of the objects of Right Hepatic Duct, Left Hepatic Duct, Common Hepatic Duct, Pancreatic Duct, Cystic Duct, Common Bile Duct and Gallbladder. Data analysis was conducted by regression test and cross tabulation. Results: The study results showed that there was an effect of varying the amount of thick slab on the scan time. The effect of varying the amount of thick slab on the image information can be seen from the statistical test that there was no effect, however descriptively there was a different on the specific per object. The image of thick slab variation of 12 was an image that had the highest value of information with the mean value of 1,988, the total value of 13.936 and a scan time of 0.46 S so that the most informative image with the most effective scan time was on the thick slab number variation of 12. Conclusion: There was an effect of variation in the number of thick slab on the scan time. More variation of the number of thick slab was followed by an increase in the value of the scan time. But there was no effect of variation in the number of thick slab on the image information, however descriptively there was a different on the specific per object which showed that the highest score for the Right Hepatic Duct, Common Hepatic Duct were in the thick slab of 12 and 30, respectivelyÂ